If it's not what You are looking for type in the equation solver your own equation and let us solve it.
y in (-oo:+oo)
(-1/2)*y-(6/5) = -1/3 // + -1/3
(-1/2)*y-(6/5)-(-1/3) = 0
(-1/2)*y-6/5+1/3 = 0
1/3-1/2*y-6/5 = 0 // - 1/3-6/5
-1/2*y = -(1/3-6/5) // : -1/2
y = (-(1/3-6/5))/(-1/2)
y = -2*(6/5-1/3)
y = -2*(6/5-1/3)
| -2x^2-18x=-1 | | 2d^2-5d-12=0 | | 3/9x^2-2x=0 | | p=2(82)+2(107) | | N(g+5)=5(g-3) | | (3x-7)/2 | | (x+1)+x=89 | | (32+p)+(3p-40)+p=522 | | 2(x^2-3x-20)=0 | | 4x+10=11x+3 | | -9x-7y=-63 | | 2(2x-4)-(x+4)= | | -2a^2+9a+7=0 | | (x+1)(x-9)=39 | | 2(2x^2-3x-20)=0 | | 12+9y=15 | | 5s^2-10s=23 | | (a^2-4a+6)+(-3a^2+13a+1)=0 | | 625000000=(125000+x)+x | | 22120/18 | | 0=-16t+8t+48 | | -3(7n+2)= | | -5x+7y=21 | | 336=(x+4)+x | | d=jqx | | x^2+y^2-4x-6y+11=0 | | (-7x+1)-(-6x-5)=1 | | 8cos(8x)=0 | | -(7x+1)-(-6y-5)=1 | | 3x+27y=54 | | 3(x^2+20)=18 | | 3+15x-2=8x+105-6x |